Fiber‐based measurement of temporal intensity and phase profiles of an optical telecommunication pulse through self‐phase modulation. Issue 4 (8th March 2018) - Baudin, Killian; Audo, Frédéric; Finot, Christophe
Abstract: We propose and experimentally validate an all‐fiber based approach to characterize the phase and intensity profiles of optical pulses. Based on three optical spectra affected by different levels of self‐phase modulation, we were able to reconstruct the temporal details of pulses typical of optical telecommunications.